Blastocytosis hominis: Unboxing Its Clinical Significance - Rozi, Muhammad Fakhrur; Darlan, Dewi Masyithah (Sumatera Medical Journal, 2019)
Abstract. Blastocystis hominisis a unicellular parasite classified as stramenopiles found in human and other mammals. The prevalence varies depending on the region, higher in developing country. The organism is transmitted via fecal-oral route by ingestion of oocyst contaminated food or water. Travelers also have high-risk of having blastocytstis infection. Based on recent studies, several proposed virulence factor are also identified but it remains elusive. The advanced technique has been used to describe its genetic variation and diversity that might be related to its clinical significance. There are 6 distinct morphological forms of Blastocystis including vacuolar, granular, ameboid, and cystic form. The cystic form is considered as an infective form of the organism. Exposure to animals is suggested as the other transmission route, consequently, the infection is also considered as zoonotic infection. It can produce broad clinical manifestation ranging from asymptomatic, self-limiting diarrhea until severe watery diarrhea, depends on host factors and the organism subtype. The organism can produce pruritus and urticaria, proved in literature. Since its pathogenicity remains unclear, conservative management is still suggested to all asymptomatic-symptomatic blastocytosis patients in accordance to patient’s immune status.